Islands within an island: Population genetic structure of the endemic Sardinian newt, Euproctus platycephalus. Issue 4 (25th January 2017) - Ball, Sarah E.; Bovero, Stefano; Sotgiu, Giuseppe; Tessa, Giulia; Angelini, Claudio; Bielby, Jon; Durrant, Christopher; Favelli, Marco; Gazzaniga, Enrico; Garner, Trenton W. J.
Abstract: The identification of historic and contemporary barriers to dispersal is central to the conservation of endangered amphibians, but may be hindered by their complex life history and elusive nature. The complementary information generated by mitochondrial (mtDNA) and microsatellite markers generates a valuable tool in elucidating population structure and the impact of habitat fragmentation. We applied this approach to the study of an endangered montane newt, Euproctus platycephalus . Endemic to the Mediterranean island of Sardinia, it is threatened by anthropogenic activity, disease, and climate change. We have demonstrated a clear hierarchy of structure across genetically divergent and spatially distinct subpopulations. Divergence between three main mountain regions dominated genetic partitioning with both markers. Mitochondrial phylogeography revealed a deep division dating to ca. 1 million years ago (Mya), isolating the northern region, and further differentiation between the central and southern regions ca. 0.5 Mya, suggesting an association with Pleistocene severe glacial oscillations. Our findings are consistent with a model of southward range expansion during glacial periods, with postglacial range retraction to montane habitat and subsequent genetic isolation. Microsatellite markers revealed further strong population structure, demonstrating significant divergence within the central region, and partial differentiation within the south. The northern population showed reduced genetic diversity. Discordance between mitochondrial and microsatellite markers at this scale indicated a further complexity of population structure, in keeping with male‐biased dispersal and female philopatry. Our study underscores the need to elucidate cryptic population structure in the ecology and conservation strategies for endangered island‐restricted amphibians, especially in the context of disease and climate change. Abstract : We have used the combination of mtDNA and microsatellite marker systems to study the population genetic structure of the Sardinian brook newt ( Euproctus platycephalus ), an endangered island endemic, applying approximate Bayesian computation to infer underlying historical and contemporary processes. Our results show previously undescribed spatiotemporal patterns of divergence, likely historical range expansion, and evidence for mitonuclear discordance.